Comparable survival outcome of metastatic colorectal cancer in Indigenous and non‐Indigenous patients: Retrospective analysis of the South Australian metastatic colorectal cancer registry. (10th August 2015) - Tomita, Yoko; Karapetis, Christos S.; Roder, David; Beeke, Carol; Hocking, Christopher; Roy, Amitesh C.; Townsend, Amanda R.; Padbury, Rob; Maddern, Guy; Price, Timothy J.
Abstract: Objective: This study aims to investigate disparities in demographics, disease characteristics, treatment and overall survival between South Australian (SA) Indigenous and non‐Indigenous patients with metastatic colorectal cancer (mCRC). Design: This employs a retrospective population study using the SA mCRC registry. Setting: The SA mCRC registry identifies mCRC patients from hospital encounters, histopathology reports, medical oncology letters, clinician notification, attendances at multidisciplinary meetings and death audits by the SA Cancer Registry. Participants: A total of 2865 adult mCRC patients including 14 Indigenous patients were identified through the SA mCRC registry between February 2006 and August 2013. Patients were linked to the SA Cancer Registry to obtain Indigenous status. Main outcome measures: Demographic, disease and treatment characteristics were compared using Chi‐squared test and t ‐test; while overall survival defined as time to any cause of death was analysed using Cox regression. Results: No difference was observed for clinical characteristics, except for a higher proportion of Indigenous patients receiving chemotherapy (85.7% versus 58.5%; P = 0.04). The rate of liver surgery was similar across the two groups (21.0% versus 15.1%; P = 0.40). The median overall survivals were equivalent (11.9 months versus 15.1 months; hazard ratio = 1.00; 95% confidence interval for hazard ratio, 0.54–1.86). Conclusions: Clinical characteristics and survival outcomes were similar between Indigenous and non‐Indigenous patients captured on the SA mCRC registry, and outcome of those who have an access to comprehensive cancer care appeared independent of Indigenous status and in line with large clinical trials. Underestimation of Indigenous cases due to their lower utilisation of cancer service could not be excluded and ultimately the accurate reporting of these patients is crucial.